2017
DOI: 10.3171/2017.2.focus16552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of robot-guided minimally invasive implantation of 2067 pedicle screws

Abstract: ObjectiveRecent studies have investigated the role of spinal image guidance for pedicle screw placement. Many authors have observed an elevated placement accuracy and overall improvement of outcome measures. This study assessed a bi-institutional experience following introduction of the Renaissance miniature robot for spinal image guidance in Europe.MethodsThe medical records and radiographs of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 25 publications
2
90
0
Order By: Relevance
“…Pedicle screw pullout strength decreases by up to 71% when the lateral wall is perforated, making accurate screw placement of utmost importance [3]. Robotic guidance with navigation assists surgeons in placing screws more consistently and accurately for posterior fixation of the spine [11][12][13][14]. The current study showed pedicle screw placement accuracy of 98%, based on GRS grading, for the first 52 patients or 292 screws placed with robotic guidance and navigation.…”
Section: Discussionmentioning
confidence: 66%
“…Pedicle screw pullout strength decreases by up to 71% when the lateral wall is perforated, making accurate screw placement of utmost importance [3]. Robotic guidance with navigation assists surgeons in placing screws more consistently and accurately for posterior fixation of the spine [11][12][13][14]. The current study showed pedicle screw placement accuracy of 98%, based on GRS grading, for the first 52 patients or 292 screws placed with robotic guidance and navigation.…”
Section: Discussionmentioning
confidence: 66%
“…6,19,21,22,26,28,29,33 Both the guide tube and drill bit are designed to anchor at the bony entrance point of the screw; however, most entrance points for pedicle screws are on the slope of the lateral aspect of the facet joint. The increased facet slope in the upper thoracic spine 29 or due to facet joint hypertrophy 19 has been associated with skiving and subsequent screw misplacement; high drilling pressure is also associated with skiving. 33 While the current study used an intraoperative CT workflow to avoid the pitfalls of preoperative CT and the need for planar fluoroscopic registration, the investigated RAN system possesses several unique features to avoid the limitations of PRA motion and instrument skiving.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies have been performed using SpineAssist or Renaissance (Mazor Robotics Ltd, Caesarea, Israel), and demonstrate accuracy rates between 96.7% and 98.9%. 10,11 The potential for perfecting accuracy is even higher when combining both navigation and robotics. Recently, there was 1 small case series published examining the use of ExcelsiusGPS in 2 patients, demonstrating 100% accuracy in screw placement in 8 screws.…”
Section: Discussionmentioning
confidence: 99%